Customizing scaffolds for game-based learning in physics: Impacts on knowledge acquisition and game design creativity - Kao, Gloria Yi-Ming; Chiang, Chieh-Han; Sun, Chuen-Tsai (Computers and education, 2017)
Scaffolds in games have the potential to facilitate learning effects in addition to assisting the gaming process. However, studies on game-based science learning usually only adopt questionnaires to evaluate scientific concepts, and use interviews or observations to assess problem solving ability, neglecting the importance of investigating game-making outcomes. We customized a digital game, “Crayon Physics Deluxe,” with varied scaffolding designs to evaluate their effects on science learning. A total of 126 participants were divided into four groups: demonstration scaffolding, non-scaffolding, marking critical features scaffolding, and the no-game group. Learning outcomes were examined in terms of physics knowledge acquisition (in the form of concept maps) and design creativity (in the form of game episode designs). Students were asked to transform their roles from problem solvers to problem designers, which might not only demonstrate their ability to solve scientific problems, but also develop their creativity potential in designing scientific puzzles. The results indicated that the marking critical features scaffolding group performed significantly better than the demonstration scaffolding group in both conceptual knowledge acquisition and the sensitivity dimension of design creativity, while the group with demonstration scaffolding scored higher in the flexibility dimension of design creativity. These findings suggest that proper scaffolds could be designed to function as learning scaffolds rather than just as gaming scaffolds, and different learning purposes require various scaffolding designs. The content of the scaffolds, as well as the timing of their provision should be carefully designed according to the game features to achieve specific instructional purposes. [Display omitted] •Customized digital games have the potential to meet specific teaching goals.•Appropriate scaffolding could enhance knowledge acquisition & design creativity.•Concept maps and game design outcomes were used to assess learning effects.•Scaffolding types and timing should be considered when customizing digital games.